Analisis Aerodinamika Kendaraan Tipe Prototype Tim Riset Hemat Energi Teknik Mesin UBB - Budi Santoso Wibowo; Jenniko Satriadi Harefa; Muhammad Zainul Abdi; Febriansyah (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The Energy Efficient Car Competition (KMHE) is a competition in the automotive sector for the prototype and urban concept categories which is held every year. In this event, participants must design, build and compete for special vehicles that can achieve maximum fuel efficiency. Regulatory standards are the basic reference in designing vehicle models. Mechanical EngineeringThe University of Bangka Belitung has a team engaged in automotive research, namely the Energy Saving Research Team. The Energy Saving Research Team has participated in an annual national-scale competition called the Energy Efficient Car Competition (KMHE) in the Gasoline combustion engine prototype category. However, in last year's competition the Energy Saving Research Team was only able to get a maximum speed of 60 km/kwh. This study aims to determine the characteristics of the air flow that occurs around the vehicle body and get the coefficient of drag value from the prototype of the Energy Saving Research Team. Thus, further development of the body design can be carried out to reduce the drag that occurs on the vehicle surface. The tool used in this study is a laptop (New Dell E7250) with software, namely Solidworks 2020 and ANSYS 2020 R1. The simulation process begins with modeling the solid-body vehicle of the Samaratungga EV. If it complies with regulatory standards, the geometry of the solid-body will be imported into ANSYS Spaceclaim for the creation of a simulation domain.